Estimation of Intra and Inter-Individual Variability of Post Mortem Skin Hydration by Corneometry - Aurélien Partoune; Anne-Françoise Donneau; Nadia Dardenne; Philippe Boxho (Arab Journal of Forensic Sciences & Forensic Medicine)
Kinetics of post mortem skin desiccation, potentially useful for post mortem interval (PMI) determination, is poorly understood. We therefore propose a preliminary study to assess intra- and inter-individual variability of post mortem skin hydration using a valid method, such as corneometry. Corneometer CM-825® (Courage & Khazaka electronic GmbH, Cologne, Germany) measures the stratum corneum hydration (SCH) by measuring its electrical capacitance, given in arbitrary units (A.U.). To assess intra- and inter-individual variability of SCH, we evaluated SCH at 19 body sites for 30 subjects with known cause of death at 6 ± 2 hours post mortem (hpm). Thirty subjects (20 males and 10 females) were selected. Mean age was 73.6 ± 9.1 years, mean BMI was 23.9 ± 5.2 kg/m2. There is a significant effect of body site on SCH values. Inter-individual variability appears to be significant, depending on the considered body site. Biological sex does not influence studied parameters, but age, BMI and cause of death influence SCH values, at various degrees depending on the considered body site. This study highlights the significant intra- and inter-individual post mortem variability in skin hydration levels. The intra-individual variability of this parameter means that the skin should not be considered as a homogeneous surface in future studies of post mortem skin desiccation. The significant inter-individual variability of this parameter probably partly explains the variations in observed PMI for this phenomenon and seems to be a major challenge in using this method to determine PMI.